SOCIAL RESPONSE APPROACH DALAM PENILAIAN FINANCIAL BUSINESS PERFORMANCE: PERSPEKTIF SHAREHOLDER WEALTH MAXIMIZATION MODEL VS CORPORATE WEALTH MAXIMIZATION MODEL - Widjaja, Liliana Inggrit (Journal of Management and Business, 2002)
First step in effective management is to determine the goals and objectives that have to achieve. Through achievement the goals, we can measure the corporate and the manager performance as performance target. The ability to explaining achievement goals depending on business performance measurement with the purpose of economic performance that containing financial aspect in monetary squad to showing value from business activities. This concept called Shareholder Wealth Maximization Model (SWM) perspective.Its contrast is Corporate Wealth Maximization Model (CWM) perspective. The different is in principal goal that should be to maximize corporate wealth. CWM perspective is broader than SWM perspective because in CWM perspective, corporate wealth measured by financial and noneconomic performance. The symmetry between financial business performance and non-economic performance: become sustainability chain to long term survival.The implementation of non-economic performance in CWM is explained by involvement of exertion to shape business ethic and social responsibility programs. The social responsiblity programs are social obligation, social reaction and social response. Corporate may achieve the highest degree of social responsiblity by social response approach when it look at social responsiblity as part of the achievement of business goals to create economic value.